Disproportionate cardiac hypertrophy during early postnatal development in infants born preterm - Aye, Christina Y L; Lewandowski, Adam J; Lamata, Pablo; Upton, Ross; Davis, Esther; Ohuma, Eric O; Kenworthy, Yvonne; Boardman, Henry; Wopperer, Samuel; Packham, Alice; Adwani, Satish; McCormick, Kenny; et al. (Pediatric research, 2017)
Background Adults born very preterm have increased cardiac mass and reduced function. We investigated whether a hypertrophic phenomenon occurs in later preterm infants and when this occurs during early development. Methods Cardiac ultrasound was performed on 392 infants (33% preterm at mean gestation 34±2 weeks). Scans were performed during fetal development in 137, at birth and 3 months of postnatal age in 200, and during both fetal and postnatal development in 55. Cardiac morphology and function was quantified and computational models created to identify geometric changes. Results At birth, preterm offspring had reduced cardiac mass and volume relative to body size with a more globular heart. By 3 months, ventricular shape had normalized but both left and right ventricular mass relative to body size were significantly higher than expected for postmenstrual age (left 57.8±41.9 vs. 27.3±29.4%, P <0.001; right 39.3±38.1 vs. 16.6±40.8, P =0.002). Greater changes were associated with lower gestational age at birth (left P <0.001; right P =0.001). Conclusion Preterm offspring, including those born in late gestation, have a disproportionate increase in ventricular mass from birth up to 3 months of postnatal age. These differences were not present before birth. Early postnatal development may provide a window for interventions relevant to long-term cardiovascular health.